The First Experience of Using a Femtosecond Laser in Pterygium Surgery - R. A. Kazakbaev (Oftalʹmologiâ, 2019)
Objective: to evaluate the functional results of the surgical treatment of pterygium using a femtosecond laser. Рatients and methods. The study included 115 patients (141 eyes) with a diagnosis of primary and recurrent stage I–III pterygium, of which 17 (19 eyes, 10.6%) had a relapse of the disease. The patients’ age was in average 54 ± 6 years, among them men and women — 56 and 44 % respectively. The same surgeon operated all patients with a femtosecond laser and fibrin glue. Results. The technique is simple to perform, the separation of the autograft from its own conjunctiva does not cause difficulties due to an accurate cut of the femtosecond laser, which helps to obtain optimal functional results in the long-term period. The size of an autograft manufactured using a femtosecond laser averaged 6 × 7 ± 1.0 mm. The edges of the graft in all cases were smooth, its thickness was the same over the entire area and amounted to 80 ± 15 μm, which facilitated the work with it and subsequent fixation. The graft was fixed using fibrin glue, the advantage of which is its hypoallergenicity, the absence of discomfort in patients and the simplicity of its use by the surgeon. Glue resorption is completed from 2 weeks to 1 month. Intra and postoperative complications were not observed in any case. The offset of autograft in the early postoperative period was also not observed in any case. Conclusion. The use of a femtosecond laser in primary and recurrent pterygium I-III surgery allows the formation of an autograft of the required thickness and size with minimal damage to the conjunctival vessels and the absence of scarring of the bulbar conjunctiva in the area of the material intake. The use of fibrin glue for fixing the autograft promotes rapid healing. The absence of relapses during the observation period and obtaining optimal functional results indicate the promise of using femtolaser technologies in pterygium surgery.